Sintesis Hidroksiapatit melalui Precipitated Calcium Carbonate (PCC) dari Cangkang Kerang Darah dengan Metode Hidrotermal Pada Variasi pH Dan Suhu Operasi - Wahyu Syafrima; Zuchra Helwani; Zultiniar Zultiniar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Hydroxyapatite Ca10(PO4)6(OH)2 is a calcium phosphate compound which is a bioactive ceramic material with high bioafinitas. Hydroxyapatite (HAp) materials used as bone implants, adsorbents and catalysts. Synthesis of hydroxyapatite can be made by using material which is rich of CaCO3 like PCC blood calm shell with a composition of 95.5% CaCO3. In this research, PCC blood calm shell which has calcium source was synthesized to HAp by hydrothermal process. pH of the reaction (10, 11, 12) and reaction temperature (140oC, 160oC, 180oC) was be varied. The outcome of synthesis was characterized by using FTIR, XRD, SEM. The results of FTIR analysis, synthesis of HAp with hydrothermal method showed the formation of hydroxyapatite in the presence of peaks PO43- dan OH-. The highest peak is obtained at pH 10 at reaction temperature of 140oC, 160oC and 180oC. XRD diffraction results in hydroxyapatite get the highest crystallinity obtained at pH 10 at temperature of 180oC with a hexagonal crystal structure and produce a more pure hydroxyapatite. SEM results showed morphology with clots and irregular round shape.Keywords : PCC blood calm shell, pH, temperature, hydroxyapatite, hydrothermal method.